Analysis of Determinants of Labor Force Participation Rate in West Nusa Tenggara Province in 2013-2022 - Wahyudi, M. Ilham; Maryam, ST.; Handayani, Tuti (West Science Business and Management, 2024)
This study aims to analyze the influence of Economic Growth, Minimum Wage, and Education Level on the Labor Force Participation Rate in West Nusa Tenggara Province in 2013-2022. The population in this study is the entire working-age population which is the labor force in West Nusa Tenggara Province. The method used in this study is a quantitative method using secondary data, the analysis technique used is multiple linear regression in the form of panel data. The data was processed using Eviews12 and the tests carried out were the Goodness Of Fit Test, Partial Test (Test T), Simultaneous Test (Test F). The results of the study show Economic Growth (X1) with a probability of 0.2536 > 0.5 which means that the Economic Growth variable does not have a significant effect on the Labor Force Participation Rate in NTB Province in 2013-2022. Furthermore, the Minimum Wage variable (X2) shows a probability value of 0.9316 > 0.5 which means that the Minimum Wage variable does not have a significant effect on the Labor Force Participation Rate in NTB Province in 2013-2022. The Education Level variable (X3) with a probabolity of 0.0000 < 0.5 shows that the Education Level variable has a significant effect on the Labor Force Participation Rate in NTB Province in 2013-2022. The results of the F test with a probability of 0.000000 show that Economic Growth, Minimum Wage, and Education Level simultaneously have a significant effect on the Labor Force Participation Rate (Y) in NTB Province.